2014
DOI: 10.2217/fmb.14.87
|View full text |Cite
|
Sign up to set email alerts
|

An Intimate Link: Two-Component Signal Transduction Systems and Metal Transport Systems in Bacteria

Abstract: Bacteria have evolved various strategies to contend with high concentrations of environmental heavy metal ions for rapid, adaptive responses to maintain cell viability. Evidence gathered in the past two decades suggests that bacterial two-component signal transduction systems (TCSTSs) are intimately involved in monitoring cation accumulation, and can regulate the expression of related metabolic and virulence genes to elicit adaptive responses to changes in the concentration of these ions. Using examples garner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…When extracellular molecules bind to these receptors a biochemical chain of reactions, better known as signal transduction, can occur (Horton et al, 2006). It has been shown that metal ions can trigger signal transduction systems which can regulate the expression of genes to evoke responses to changes in the metal ion concentration in bacteria (Singh et al, 2014). Also in our study, effects of zinc on signal transduction were observed.…”
Section: Signal Transductionsupporting
confidence: 67%
“…When extracellular molecules bind to these receptors a biochemical chain of reactions, better known as signal transduction, can occur (Horton et al, 2006). It has been shown that metal ions can trigger signal transduction systems which can regulate the expression of genes to evoke responses to changes in the metal ion concentration in bacteria (Singh et al, 2014). Also in our study, effects of zinc on signal transduction were observed.…”
Section: Signal Transductionsupporting
confidence: 67%
“…To maintain the copper homeostasis, cytosolic copper is precisely regulated by resistance proteins. The twocomponent system was previously confirmed as the key regulatory system for the extra-cytoplasmic sensing of elevated copper ion and can regulate the expression of related genes to elicit adaptive responses to changes in the concentration of copper (Chaplin et al 2015;Singh et al 2014). Here, we found a total of 8 genes in the genome of S. erythraea NRRL23338 that are potentially involved in copper metabolism.…”
Section: Determination Of the Relative Transcript Levels Of Copper-rementioning
confidence: 65%
“…Some of the targets (Psest_0600 and Psest_1596) belong to P‐type ATPase family of transporters, which contains copper tolerance genes from Escherichia coli and other bacteria (Cha and Cooksey, ; Rowland and Niederweis, ). Interestingly, co‐evolution of TCSs and transporters has been explored in Firmicutes TCS and ABC transport systems (Dintner et al ., ; Gebhard, ), and has also been observed in other bacteria (Singh et al ., ). The second prominent category of copper resistance genes involved in copper tolerance includes multicopper oxidases.…”
Section: Resultsmentioning
confidence: 97%
“…At the same time, several known copper resistance genes (e.g., copA1 , copB1 , copA2 , copB2 ) did not demonstrate a copper‐specific phenotype in that study. Transition metals are known to have interrelated and complex impact on microbial physiology often triggering overlapping response (Singh et al ., ). Coordinated interactions may be required for the optimal final response and has been reported for the copper‐ and zinc‐responsive regulators in P. aeruginosa (Caille et al ., ) and copper‐responsive regulators in Salmonella sp (Pezza et al ., ).…”
Section: Introductionmentioning
confidence: 97%